Analisis Strategi Pemasaran Agen Asuransi Melalui Komunikasi Pemasaran Personal Selling Dalam Penjualan Polis Asuransi pada PT Pudential Syariah Binjai - Ramadhani, Tri Azmi; Lubis, Fauzi Arif (Ikatan Da'i Indonesia, 2023)
Insurance is a product of goods or services that are visible and there is no clarity on the goods, therefore many people do not trust insurance for various reasons. Some of the most common reasons found related to insurance are procedures that are considered difficult to process claims, and premium rates that are too high. Sales of insurance products is one of the product sales whose development is largely determined by the company's efforts in marketing its products to the public. PT. Prudential Syariah Binjai conducts personal selling with the aim of explaining the products offered. Personal Selling is one of the promotional mix which is an oral presentation by the company to one or several prospective buyers with the aim that the goods or services offered can be sold. The data analysis method used is descriptive method with qualitative data that has been obtained through direct data from the company. The results showed that the personal selling activities carried out by PT. Prudential Syariah Binjai not only provides presentations or explains in detail but also provides seminars and training to prospective customers.